1985
DOI: 10.1063/1.335910
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal gettering in silicon-on-insulator structures formed by oxygen implantation into silicon

Abstract: Gettering of chromium and copper metal impurities to the damaged regions surrounding an implanted buried oxide has been investigated. Cr tends to segregate to the surface Si-SiO2 interface; only a small fraction moves to the damaged regions surrounding the buried oxide. Cu segregates to the damaged regions more readily; in addition, a large fraction of the implanted Cu moves to a location several micrometers beneath the buried oxide layer. The buried oxide does not appear to stop the movement of the Cu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…These results are strictly applicable only to Newtonian liquids that do not evaporate during spin coating; however, they are in-good agreement with the planarization properties found for spin-coated positive photoresist and polyimide films (6)(7)(8)(9)(10)(11)(12)(13). Thus, the film profiles over 1 t~m deep topographic gaps midway between the center and the edge of a spinning 4 in.…”
Section: Uncoated Substratesupporting
confidence: 78%
See 2 more Smart Citations
“…These results are strictly applicable only to Newtonian liquids that do not evaporate during spin coating; however, they are in-good agreement with the planarization properties found for spin-coated positive photoresist and polyimide films (6)(7)(8)(9)(10)(11)(12)(13). Thus, the film profiles over 1 t~m deep topographic gaps midway between the center and the edge of a spinning 4 in.…”
Section: Uncoated Substratesupporting
confidence: 78%
“…In optical lithography, resolution or minimum linewidth (l) and depth of focus (8) are related to the exposure wavelength (X) and the numerical aperture (NA) of the lens as shown below I a X/NA [1] ~ X/(NA) 2 [2] Decreasing the exposure wavelength or increasing the NA of the lens to improve resolution will lead to a decrease in depth of focus and planarization of substrate topography may become necessary as optical lithography is pushed toward its resolution limits (1). Possibly a more immediate need for planarization is for some interlevel metal connection schemes that use etch-back steps (5,6). In these schemes a thick, bottom organic layer planarizes the substrate topography, and a thin top layer is used for imaging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the intrinsic implantation damage in SIMOX wafers can serve as gettering sites for the transition metals. [5][6][7] However, the gettering efficiency of such intrinsic gettering sites varies with the SIMOX fabrication process used and there is no effective gettering in the BOX of bonded SOI. 6 Therefore, more favorable trapping sites should be introduced to reduce the concentration of metal impurities in the top Si layer to an acceptable level.…”
Section: Introductionmentioning
confidence: 99%
“…Minority carrier lifetime measurements (2) imply that, if metals are present, efficient gettering occurs during postimplantation annealing or silicon epitaxy to reduce their concentration sufficiently that little degradation of lifetime is observed. Recent work (5,6) has shown that copper, which was intentionally implanted into the silicon surface layer ofa SOI structure formed by oxygen implantation, diffuses through the oxide layer during subsequent annealing and tends to segregate in the substrate silicon. Recent work (5,6) has shown that copper, which was intentionally implanted into the silicon surface layer ofa SOI structure formed by oxygen implantation, diffuses through the oxide layer during subsequent annealing and tends to segregate in the substrate silicon.…”
mentioning
confidence: 99%